Kształtowanie się socjalistycznej demokracji przedstawicielskiej w świetle rozwoju konstytucyjnego państw socjalistycznych: [Structure of Socialist democracy based on representaton in the light of constitutional development of a socialist state] (Studia Prawnicze / The Legal Studies, 1981)
The Author presents the period of creation of democratic system of people’s representation and points out to the principal features of constitutional solutions of the years 1946-1952. These are: system of representation as a main form of realization of the souvereignty of the working people; combination of democracy based on representation with elements of direct democracy; linking of the law- making activity with exercise of power; giving the representation (local one included) superior position in the hierarchy of state organs; homogenous structure of the system of representation resulting from the principle of democratic cen- tralism and from the guaranty of equal treatment of the nations in multi-national states.Further strengthening and developing of socialist forms of democracy based on representation can be observed in the stage of building socialist society. And so, e.g, social composition of the representation was strengthened which is con- nected with the process of ameliorating the system of elections and with the increase of the role of people’s (national) fronts. Further deepening of ties between the representation and direct democracy occurs as well. This is reflected in constitutional définition of the ties linking the voters with their representatives and especially with the working collectives. Closer relation with direct democracy is also reflected in democratization of the law-making process.Development of socialist constitutionalism helps to strengthen superiority of the representation over the organs of state administration and unification of the system of representation.In multi-national states, federalism constitutes an important source of insti- tutional widening of the forms of socialist democracy.Further development of state and of socialist democracy in the conditions of sicentific and technical revolution brings up new tasks before socialist constitu- tional law. One of the most characteristic directions of development of socialist democracy is the increase of the role of direct participation of the citizens in managing and administrating state affairs, especially on the local level, and widening of self-administration elements of socialist democracy based on repre- sentation.Building of developed socialism means creating all-national democracy. This process requires thorough theoretical studies and among the principal issues to study we can point out criterions according to which democracy can be considered developed. This is the issue undertaken already by prof. S. Zawadzki.